Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1089/scd.2015.0277
|View full text |Cite
|
Sign up to set email alerts
|

Polycomb Protein BMI1 Regulates Osteogenic Differentiation of Human Adipose Tissue-Derived Mesenchymal Stem Cells Downstream of GSK3

Abstract: Polycomb proteins such as the B lymphoma Mo-MLV insertion region 1 homolog (BMI1) are essential chromatin factors for the self-renewal and differentiation of embryonic and adult stem cells. BMI1 also plays a critical role in osteogenesis as Bmi1-deficient mice display a skeletal phenotype caused by the exhaustion of the mesenchymal stem cell pool. In this study, we have studied the role of BMI1 in the osteogenic differentiation of human adipose tissue-derived mesenchymal stem cells (hASCs). BMI1 protein, but n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 74 publications
0
6
0
Order By: Relevance
“…It has recently been shown that in vitro overexpression of BMI1 enhanced osteogenesis of human adipose tissue‐derived MSCs, whereas knockdown of BMI1 reduced their osteogenic differentiation . Our previous study showed that Bmi1 deficiency reduced osteogenesis of BM‐MSCs with downregulation of osteogenic gene expression .…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…It has recently been shown that in vitro overexpression of BMI1 enhanced osteogenesis of human adipose tissue‐derived MSCs, whereas knockdown of BMI1 reduced their osteogenic differentiation . Our previous study showed that Bmi1 deficiency reduced osteogenesis of BM‐MSCs with downregulation of osteogenic gene expression .…”
Section: Discussionmentioning
confidence: 93%
“…Recently, study showed that the upregulation of BMI1 induced by hypoxic‐cultures stimulated the proliferation of human umbilical cord blood‐MSCs, whereas knockdown of BMI1 in hypoxic cells inhibited their proliferation . in vitro study also showed that overexpression of BMI1 resulted in osteogenic priming of human adipose tissue‐derived MSCs under nondifferentiating conditions and enhanced osteogenesis upon differentiation, whereas knockdown of BMI1 reduced their osteogenic differentiation . However, it is unknown whether overexpression of Bmi1 in MSCs in vivo affects the proliferation and differentiation of MSCs.…”
Section: Introductionmentioning
confidence: 99%
“…BMI1 expression also increases during osteogenic differentiation of human adipose derived stem cells (hASCs) in vitro. Overexpression of BMI1 enhanced osteogenic differentiation of hASCs and increased BMP2 and WNT11 expression . BMI1 knockout mice have skeletal growth retardation, with decreased trabecular bone volume and bone mineral density .…”
Section: Epigenetic Targeting As Treatment Of Mmbdmentioning
confidence: 95%
“…5 Research Center of Engineering and Technology for Computerized Dentistry Ministry of Health, Beijing, China. 6 NMPA Key Laboratory for Dental Materials, Beijing, China. 7 Department of Prosthodontics, Peking University School and Hospital of Stomatology, Beijing, China.…”
Section: Acknowledgementsmentioning
confidence: 99%
“…As we know, human adipose-derived stem cells (hASCs) have multilineage differentiation potentials and good application prospects for bone regeneration [1][2][3] because of their abundant sources and easy access for clinical uses [4]. Though plenty of signaling pathways, such as Wnt/β-catenin signal [5], glycogen synthase kinase 3 signal [6], bone morphogenetic protein (BMP) signal [7][8][9], NOTCH signal [10,11], and extracellular regulated protein kinases signal [7,12,13] have been demonstrated to dominate osteoblastic differentiation of hASCs, considerable research is still necessary to reveal intricate interactions between various signals and make further advances in hASC-based cell therapy.…”
Section: Introductionmentioning
confidence: 99%